2020
DOI: 10.1051/parasite/2020008
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii infection in sheep in Inner Mongolia Province, China

Abstract: Toxoplasma gondii is an important zoonotic parasite that can infect almost all warm-blooded animals, including humans, and infection may result in many adverse effects on animal husbandry production. Animal husbandry in Inner Mongolia is well developed, but data on T. gondii infection in sheep are lacking. In this study, we determined the seroprevalence and risk factors associated with the seroprevalence of T. gondii using an indirect enzyme-linked immunosorbent assay (ELISA) test. A total of 1853 serum sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
2
8
1
Order By: Relevance
“…The results showed that ducks 1<years≤2 of age (OR: 4.1; 95% CI: 1.0–17.2) had four times higher risk of being positive compared with ducks ≤1 year-old, indicating that age may be a risk factor for T. gondii infection, in agreement with previous studies ( 40 43 ). Age is widely considered as a risk factor for high infection rates of T. gondii ( 44 , 45 ). This might be attributed to increased frequency of exposure to the infectious T. gondii oocysts or the cumulative effect of the time period during which an animal can be exposed to the parasite ( 43 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that ducks 1<years≤2 of age (OR: 4.1; 95% CI: 1.0–17.2) had four times higher risk of being positive compared with ducks ≤1 year-old, indicating that age may be a risk factor for T. gondii infection, in agreement with previous studies ( 40 43 ). Age is widely considered as a risk factor for high infection rates of T. gondii ( 44 , 45 ). This might be attributed to increased frequency of exposure to the infectious T. gondii oocysts or the cumulative effect of the time period during which an animal can be exposed to the parasite ( 43 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adopted stray cats in our study live in Khao Suan Kwang district next to Khon Kaen Zoo, which is a rural area far away from Mueang district, about 50 km. In the zoo, many animals can be intermediate hosts of T. gondii, such as sheep [30], goats [31], rusa deer [32], and other Felidae [33], among others. Furthermore, a high incidence of T. gondii infection in captive felids, that is, 15.4%-18.84%, was reported in Thailand [18,34].…”
Section: Discussionmentioning
confidence: 99%
“…The Inner Mongolia Autonomous Region holds a significant position in the livestock sector of China. The livestock economy is regarded as one of the crucial industries in the region and serves as the primary economic backbone for the local herders [ 2 ]. Nonetheless, several studies have shown that grazing sheep may not receive sufficient mineral intake, such as copper (Cu), from natural forages to support their optimal growth and development [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%